A review of Sciurus Group studies on the red squirrel (Sciurus vulgaris): presence, population density and colour phases in Lombardy (Italy) - Biancardi, Carlo M.; Gnoli, Claudio G. (Natural history sciences : atti della Società italiana di scienze naturali e del Museo civico di storia naturale in Milano, 2016)
During the nineties of the last Century, under the inspiration of Luigi Cagnolaro, it had been founded a “Sciurus group”, within the Research Centres of the Società Italiana di Scienze Naturali. Aim of the group was to start a campaign of researches on red squirrel populations in Lombardy, Italy promoting field master thesis on various topics: colour phases and indirect estimations of population densities. The researches were carried out during 10 years in 5 study areas. An investigation and census with questionnaires were started in parallel, with the collaboration of Forest Guards (CFS), Ecological Guards (GEV) and students of biological and natural sciences. The results were published in Italian or exposed in national and international congresses. This review has the purpose to show and critically discuss the overall results, and make them available to a broader audience. The dark colour phase, in the red squirrel, resulted associated to elevation and conifer woodlands, according to the thermoregulation theory, which consider the dark fur thicker and more suitable in cold environments. Squirrel population densities are subject to periodical fluctuations, in conifer woodlands, due to cones availability. Cone crops are subject to cycle with years of great production followed by years of lean. The recorded squirrel densities are middle-lows, but in line with data from similar environments.